Analysis of Pending Claims Due to Incompatibility of Diagnostic and Action Codes in Inpatients in Hospitals - Puguh Ika Listyorini; Nadia Arifah Ramadhan (LPPM Universitas Duta Bangsa Surakarta, 2022)
This research was conducted at UNS Sukoharjo Hospital. Based on the preliminary study, it was found that 19.5% of the claims filed were pending in inpatient claims and 31% were due to coding cases. This study was conducted to determine pending claims due to coding discrepancies in hospitalized National Health Insurance patients. This is a case study research type with a qualitative research design. Data were taken by observation and interviews with the head of the medical record installation room, coding officer, head of the guarantee installation room, and the verifier of the Health Insurance Administration. The data collected, presented descriptively, and analyzed using content analysis techniques. The results showed that the coding of claim files had been carried out according to hospital standards. Submission of the claim file is carried out after verification by the internal verifier. The pending claim occurs due to a mismatch in coding caused by the need for a join code, an error in determining the main diagnosis, the need for confirmation of the action code, and the need for confirmation of supporting reports. Other influencing factors are support from colleagues, technology support, limited knowledge, and lack of staff training, as well as system changes and problematic servers both from hospitals and from Health Insurance Providers. The conclusion is that there are still pending claims caused by coding cases, so it is better for officers to take coding training and perform server maintenance.